A VIOLÊNCIA NOS ESTÁDIOS DE FUTEBOL NA PERSPECTIVA DOS POLICIAIS MILITARES DE CURITIBA: UM ESTUDO DE CASO - Netto, Alfredo Euclides Dias (2009)
During many years the sportive events had been left of side for the social scientists, however, the sport/soccer blunt as one of the biggest social phenomena of the present time, involving in its bigger public events each time, which if they leave to take for the emotions, being generated innumerable acts of violence. In this context some studies concerning the violence of the twisted ones organized in soccer sta-diums are had, however this research retakes this quarrel under a new prism, that is, under the point of view of the military policemen. Being the generating problem of this study centered in the understanding that the military policemen possess of the vi-olence generated for the Twisted ones Organized. In the construction of the research proper methods to a qualitative research of exploratory matrix had been used. To reach the objective considered initially it was looked to understand the violence meaning, the violence in the sport and more specifically in the soccer, and for this a bibliographical research was carried through . After that, basing in the theoretical re-ferential of Elias, categories had been arisen that could support the quarrel with the collected data, in the objective to arrive at the understanding that the military police-men possess on the violence of the Twisted ones Organized, being raised the follow-ing categories: psycho genesis, socio genesis, to be able, outsiders and the control of the violence. Searching to deepen the thematic one of the violence of the twisted ones organized in soccer stadiums a study of case on the classic Atletiba was carried through (game between the Coritiba Foot Ball Club e the Club Athletic Paranaense) carried through in the seventeenth day of October of a thousand nine hundred and ninety and nine, in the stadium Major Antonio Couto Pereira, in the city of Curitiba, game this considered one of the most violent occurrences in the state of the Paraná. For this study initially one searched to rescue the history and origin of the Twisted ones Organized of the Coritiba Foot Ball Club and the Athletic Club Paranaense and the legality of the action of the Military Policy in sport's squares (stadiums), beyond portraying under the different perspectives the facts of occurred violence in this clas-sic. On the basis of the raised theory was become fulfilled interviews, half-structuralized, applied the five military policemen, who were working in that game specify, with the objective to verify the perception that they possess concerning the categories in relation to the described environment. After he analyzes of the data concluded that the military policemen possess knowledge who are the state repre-sentatives detainer of the monopoly of the violence, that they possess the knowledge of the use of the legal violence and the abuse, however in certain confrontations they finish if exceeding, and that they possess a preconception on the twisted ones orga-nized, seeing them as, people wilderness, riotous that goes to stadiums with the ob-jective to provoke tumults, fight. Being many times the favor of the extinguishing of these twisted ones.